2013
DOI: 10.2169/internalmedicine.52.8848
|View full text |Cite
|
Sign up to set email alerts
|

Portal Biliopathy Diagnosed Using Color Doppler and Contrast-enhanced Ultrasound

Abstract: Portal biliopathy is a morphological abnormality of the biliary ductal and gallbladder wall associated with portal hypertension. A patient with essential thrombocythemia was initially diagnosed with extrahepatic portal vein obstruction (EHPVO). The contrast-enhanced computed tomography (CT) findings were similar to those of cholangiocarcinoma or sclerosing cholangitis. However, color Doppler and contrast-enhanced ultrasound (US) were more specific. The paracholedocheal veins around the bile ducts appeared as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Thereafter, the whole bile ducts gradually become enhanced ( fig 9). Using this imaging method, a clear differentiation between the dilatation of paracholedocheal veins and pericholedocheal venous plexuses can be distinguished [16].…”
Section: Portal Hypertensive Biliopathy (Phb)mentioning
confidence: 99%
“…Thereafter, the whole bile ducts gradually become enhanced ( fig 9). Using this imaging method, a clear differentiation between the dilatation of paracholedocheal veins and pericholedocheal venous plexuses can be distinguished [16].…”
Section: Portal Hypertensive Biliopathy (Phb)mentioning
confidence: 99%
“…Nunoi H et al [11] described a patient with PB-associated with the morphological abnormality of the biliary duct and GB associated with PH that presented with essential thrombocythemia, initially diagnosed with extrahepatic portal vein obstruction. The contrast-enhanced CT findings were similar to those of cholangiocarcinoma or sclerosing cholangitis.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Presently there is no role for intravenous cholangiography. Shin SM in their study of MRI features of PB showed that MR cholangiography and 3D gradient-echo imaging not only detect portal vein occlusion, but cavernous transformation, and GB varices and other associated bile duct abnormalities [4]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…Findings of PTB and EHPVO can be well described by colour Doppler flow imaging, endoscopic retrograde cholangiopancreaticography (ERCP), CECT and MRI [27][28][29]. We diagnosed this case with MRCP and CECT portovenography [30,31].…”
Section: Discussionmentioning
confidence: 99%